Changes in serum cartilage oligomeric matrix protein (COMP), plasma CPK and plasma hs-CRP in relation to running distance in a marathon (42.195 km) and an ultra-marathon (200 km) race - Kim, H. J.; Lee, Y. H.; Kim, C. K. (European Journal of Applied Physiology, 2009)
Marathon running is frequently associated with numerous cellular changes, but little information is available on the effects of exercise-mediated prolonged impact-stress on cartilage integrity. This study was undertaken to evaluate muscle and cartilage damage with different running distances. Twenty male marathoners and ultra-marathoners participated in the study. Serum COMP and plasma CPK and hs-CRP were measured as markers of cartilage and muscle damage and inflammation. Serum COMP was increased 1.6-fold at 10 km during a marathon race and declined to the pre-race level after 2 days recovery. In contrast, serum COMP was increased 1.9-fold after a 200-km race and maintained until day 3 of recovery, only returning to the pre-race level on day 6. Plasma CPK was increased at 10 km of the marathon race and up to threefold at the end of the race. This was further increased on day 1, only returning to pre-race level on day 6. Plasma CPK was increased 35-fold at the end of the 200-km race and remained increased until day 5. There was no change in plasma hs-CRP during the marathon race, but this was increased 3.4-fold by day 1, returning to the pre-race level on day 4. Plasma hs-CRP increased 40-fold by the end of the 200-km race and was still increased on day 6 of recovery. Therefore, longer distance running may induce more impact-stress both on muscle and cartilage. Further, the required time for recovery may vary with running distance and the tissue type, e.g. cartilage or skeletal muscle as in this case.